2018
DOI: 10.1021/acs.jpca.8b08740
|View full text |Cite
|
Sign up to set email alerts
|

Single-Crystal X-ray Diffraction Studies of Solvated Crystals of C60 Reveal the Intermolecular Interactions between the Component Molecules

Abstract: The solid-state structures of seven solvates of C 60 (C 60 •4tetrachloroethylene, C 60 •2tetrachloroethylene, C 60 • 3benzene, C 60 •n-pentane, C 60 •diethyl ether, C 60 •chlorobenzene, and C 60 •benzene•dichloromethane) were determined by single-crystal X-ray diffraction at low temperature. At 90 K, the fullerene and solvate components are generally wellordered and do not show the orientational disorder that plagues similar structures determined at room temperature. Interactions between the solvate molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 57 publications
(89 reference statements)
2
13
0
Order By: Relevance
“…Marks and co‐workers reported that spin‐coated Y6 neat films show an average μ e of 2.15×10 −4 cm 2 V −1 s −1 in ambient conditions, similar to the values of IDTTs (10 −5 ∼10 −4 cm 2 V −1 s −1 ) [17] but much lower than those of fullerenes ( μ e >10 −3 cm 2 V −1 s −1 ) [16] . The lower μ e of Y6 than fullerenes can be probably explained by the unique fullerene film microstructure [42] . Yip and co‐workers [35] used the electron‐only device structure ITO/AI/pristine or blend films/LiF/AI, and the hole‐only device structure ITO/PEDOT:PPS/pristine or blend films/MoO 3 /Ag, and determined the mobility by fitting the dark current to the model of a single carrier SCLC.…”
Section: Diode Performancesupporting
confidence: 70%
See 1 more Smart Citation
“…Marks and co‐workers reported that spin‐coated Y6 neat films show an average μ e of 2.15×10 −4 cm 2 V −1 s −1 in ambient conditions, similar to the values of IDTTs (10 −5 ∼10 −4 cm 2 V −1 s −1 ) [17] but much lower than those of fullerenes ( μ e >10 −3 cm 2 V −1 s −1 ) [16] . The lower μ e of Y6 than fullerenes can be probably explained by the unique fullerene film microstructure [42] . Yip and co‐workers [35] used the electron‐only device structure ITO/AI/pristine or blend films/LiF/AI, and the hole‐only device structure ITO/PEDOT:PPS/pristine or blend films/MoO 3 /Ag, and determined the mobility by fitting the dark current to the model of a single carrier SCLC.…”
Section: Diode Performancesupporting
confidence: 70%
“…[16] The lower μ e of Y6 than fullerenes can be probably explained by the unique fullerene film microstructure. [42] Yip and co-workers [35] used the electron-only device structure ITO/AI/pristine or blend films/LiF/ AI, and the hole-only device structure ITO/PEDOT:PPS/pristine or blend films/MoO 3 /Ag, and determined the mobility by fitting the dark current to the model of a single carrier SCLC. The mobility was calculated from the slope of the J 1/2 -V curves.…”
Section: Diode Performancementioning
confidence: 99%
“…Phase transitions in crystals containing fullerenes were observed for several cases, such as, Li@C 60 /NiOEP, 12 C 60 /S 8 , 13 , C 60 /CS 2 , 14 C 60 /C 6 H 6 , 15 C 60 /C 2 Cl 4 . 16 C 60 /CoOEP was reported more than two decades ago. 17 .…”
mentioning
confidence: 99%
“…Two crystal habits form: black hexagonal crystals of C60(SnI4)2 at the bottom of the jar, and black needle-like crystals on the sides of the jar which have a unit cell corresponding to the C60-pentane intercalation compound C60(C5H12). 37 The amount of C60(C5H12) that crystallizes can be reduced by layering a small amount of benzene on top of 1,2dichlorobenzene before layering pentane.…”
Section: Methodsmentioning
confidence: 99%